Prevalence and Risk Factors for Presumptive Ascending/Descending Myelomalacia in Dogs after Thoracolumbar Intervertebral Disk Herniation. (1st February 2017) - Balducci, F.; Canal, S.; Contiero, B.; Bernardini, M.
Abstract : Background: Ascending/descending myelomalacia (ADMM) is a severe complication of thoracolumbar intervertebral disk herniation (TL‐IVDH) in dogs. Hypothesis/Objectives: To investigate the prevalence and risk factors for ADMM in nonambulatory dogs with surgically treated TL‐IVDH. Animals: Six‐hundred and fifty‐two client‐owned dogs evaluated for TL‐IVDH that underwent decompressive spinal surgery. Methods: Retrospective medical record review from February 2007 through December 2015. Results: Thirteen dogs developed ADMM, with an overall prevalence of 2.0%. The prevalence of ADMM was 0% in dogs with neurological signs graded 1 or 2 at admission or before magnetic resonance imaging (MRI) or surgical procedures, 0.6% in dogs with neurological signs graded 3, 2.7% in dogs with neurological signs graded 4, and 14.5% in dogs with neurological signs graded 5. Age (<5.8 years), neurological status (grade 5), site of disk herniation (L5‐L6), duration of clinical signs before becoming nonambulatory (<24 hours), detection of intramedullary T2‐weighted (T2W) hyperintensity, and a T2 length ratio >4.57 were significant risk factors in the univariate analysis for development of ADMM. Conclusions and Clinical Importance: The factors identified in this study may be useful for the prediction of ADMM. Multicenter studies with a higher number of dogs with ADMM are required to confirm these data.